The impacts of human-induced disturbances on spatial and temporal stream water quality variations in mountainous terrain: A case study of Borcka Dam Watershed - Ozalp, Mehmet; Yildirimer, Saim; Yuksel, Esin Erdogan (Cell Press, 2023)
Unaltered watersheds with natural vegetation cover (forest, grasslands, etc.) provide several ecological benefits in addition to providing freshwater, controlling water levels, and supporting flourishing streamside ecosystems. However, as in many watersheds in the World, the research area in this study, the Borcka Dam Watershed (BDW), has been affected by many human-induced disturbances affecting a wide area of forest and grassland areas as well as soil and water resources. Therefore, the objective of this study was to assess and evaluate the possible effects of anthropogenic disturbances, particularly on annual changes in water discharge, some water quality parameters, and total suspended sediment (TSS) amounts in the main streams of four sub watersheds (Fabrika, Godrahav, Hatila, and Murgul) and the reservoir of the dam. In addition, we intend to confirm that land use change and/or transformation play a significant role in influencing stream water quality. The YSI/Professional-Plus, a portable water quality measurement device, was used to determine the amounts of pH, dissolved oxygen (DO), total dissolved substance (TDS), ammonium (NH4-N), nitrate (NO3-N), salinity, electrical conductivity (EC), and temperature besides measuring discharge and total suspended sediments (TSS) from a total of 27 sampling points in the field. Although the results revealed that the annual mean values of all water quality parameters for all four streams were mostly in good condition, for some time and points of the measurements, several parameters were found to be above the official water quality standards due to the intensive aforementioned anthropogenic activities, particularly in the stream waters of Murgul (e.g. pH and TSS being 10,84 and 236 mg/L, respectively) and Fabrika (e.g. EC of 412 & mu;s/cm; DO of 4.44 mg/L; 14 ml of NO3-N) sub-watersheds. These outcomes indicate that these two sub-watersheds have been impacted more severely by the human-induced disturbances compared to Hatila and Godrahav sub-watersheds.
Keywords: Stream water quality; Sediment yield; Mountainous watersheds; Human-induced disturbances; Land use